O MERCADO DE DISTRIBUIÇÃO DE ENERGIA ELÉTRICA NO MARANHÃO: um estudo sobre a proatividade ambiental - Bezerra Júnior, José Tavares (2013)
The environmental issue has been gaining importance in several respectable social spheres today. This is due, among other causes, by significant changes perceived in the environment, which are derived from changes in consumption patterns of the population, increasing the supply of credit, radical changes in temperature, among others. In this context, companies adopt behavior patterns that vary between acting reactively or follow a proactive approach. This research proposes a study on the environmental proactivity and from proposed by González - Benito and González - Benito (2006) model, seeks to identify the determinants of environmental proactivity in the electricity distribution market in the state of Maranhão and simultaneously verify the existence or absence thereof. The study was guided by tripod practices of environmental proactivity segregated practices in Planning and Organization, Operational and Communication. Moreover, the determinants of environmental proactivity were marked by all of Organizational Characteristics (firm size, degree of internationalization, position in the value chain, strategic management and attitude) of External Factors (environmental impact, environmental legislation and geographic location) Pressure and Stakeholders (internal, external, primary and secondary). A strong influence of stakeholders in the process of causal, relative influence of organizational characteristics and low influence of external factors, and the results found on the influence of stakeholders corroborated with the literature on the subject.